DNA replication in Physarum polycephalum: UV photolysis of maturing 5-bromo-deoxyuridine substituted DNA. - Funderud, S (1978)
Combinations of 5-bromodeoxyuridine (BrdUrd) and 3H-deoxyadenosine (3H-DAdo) short pulses were given in the synchronous DNA-replication period of Physarum polycephalum. After a chase period, UV-photolysis products were analyzed on alkaline sucrose gradients. This strategy has allowed the following conclusions. a) at the time of master-initiation of DNA replication, points separated by 1.1-2.2x10(7) daltons of single strand DNA may initiate DNA synthesis. b) among these, only selected groups of replicons actually proceed in DNA replication at this time, while others appear to hold (later temporal sets of replicons). The origins of the ones that proceed in replication are separated from each other by a distance corresponding to 1.1-2.x10(7) daltons. c) regions in actual replication are separated from each other by increasing distances (up to 1.5x10(8) daltons single strand DNA) at later times in S.